2019
DOI: 10.14393/bj-v35n6a2019-42425
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal activity of Myrcia ovata essential oils and their major compounds against pathogens of citrus, sweet potato, and coconut

Abstract: Myrcia ovata, an endemic species to the Brazilian Atlantic Forest, presents antifungal properties. The phytopathogens Colletotrichum acutatum, Plenodomus destruens, and Thielaviopsis paradoxa are responsible for the diseases citrus postbloom fruit drop, sweet potato foot rot, and coconut stem bleeding, respectively. The antifungal activity of the essential oils of five M. ovata chemotypes (MYRO-159, nerolic acid chemotype; MYRO-180, nerolic acid + linalool chemotype; MYRO-388, geraniol chemotype; MYRO-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The activity of these compounds as a repellent, odor character, insecticides, and nematicides have already been reported earlier by Huang et al (2018) and Mravčáková et al (2021). Similarly, the compounds, dodecadienal, undecane, and nerolic acid observed throughout metabolite profiles in the present study have already been reported as nematicidal, antibacterial, and antifungal compounds (Caboni et al, 2012;White et al, 2019;Sarsaiya et al, 2020). Correspondingly, A. thaumasia At_RK secreted non-volatile compounds such as aganing, talathermophilin, and dactylarin found in other nematophagous fungi, A. entomopa, Talaromyces thermophilus, and Dactylaria lutea (Kettner et al, 1973;Degenkolb and Vilcinskas, 2016;Wang X. et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The activity of these compounds as a repellent, odor character, insecticides, and nematicides have already been reported earlier by Huang et al (2018) and Mravčáková et al (2021). Similarly, the compounds, dodecadienal, undecane, and nerolic acid observed throughout metabolite profiles in the present study have already been reported as nematicidal, antibacterial, and antifungal compounds (Caboni et al, 2012;White et al, 2019;Sarsaiya et al, 2020). Correspondingly, A. thaumasia At_RK secreted non-volatile compounds such as aganing, talathermophilin, and dactylarin found in other nematophagous fungi, A. entomopa, Talaromyces thermophilus, and Dactylaria lutea (Kettner et al, 1973;Degenkolb and Vilcinskas, 2016;Wang X. et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Identification of volatile organic compounds (VOCs) of A. thaumasia and T. cylindrosporum using GC-MS analysis. Ferula assa-foetida oil, having antibacterial activity against Streptococcus mutans, S. sanguis, S. salivarius, S. sobrinus, and Lactobacillus rhamnosus(Daneshkazemi et al, 2019) Salmali Niryasa having antimicrobial activity against Klebsiella pneumoniae, Staphylococcus aureus, E. coli, and Candida albicans(Divya and Prabhu, 2015) It was found in Myrcia ovata oils having antifungal activity against Colletotrichum acutatum, Plenodomus destruens, and Thielaviopsis paradoxa(White et al, 2019) Salmali niryasa having antimicrobial activity against Klebsiella pneumoniae, Staphylococcus aureus, E. coli, and Candida albicans(Divya and Prabhu, 2015) …”
mentioning
confidence: 99%